1971
DOI: 10.1063/1.1660706
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Clustering in Silicon

Abstract: Large decreases in the conductivity of arsenic-doped silicon have been observed during 500–970°C heat treatments. The rate of conductivity change depends upon the prior quenching rate from diffusion temperature to room temperature. These conductivity changes are reversed by higher-temperature treatments. The relationship between the electrically active arsenic, as calculated from the conductivity, and the total arsenic is shown to be consistent with a model of substitutional arsenic atoms being nonionized when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

1972
1972
1997
1997

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(28 citation statements)
references
References 4 publications
2
26
0
Order By: Relevance
“…It has been found that the location of As atoms in the Si lattice and the accompanying electrical behavior at high concentrations is a complicated function of diffusion (1)(2)(3) temperature. .em at room temperat-ure into three types of precisely to the projected range (Rp) of 100 keV As and the depth of the original amorphous/crystalline interface (Fig.…”
Section: + Now At Microelec~ronics Center Of North Carolinamentioning
confidence: 99%
“…It has been found that the location of As atoms in the Si lattice and the accompanying electrical behavior at high concentrations is a complicated function of diffusion (1)(2)(3) temperature. .em at room temperat-ure into three types of precisely to the projected range (Rp) of 100 keV As and the depth of the original amorphous/crystalline interface (Fig.…”
Section: + Now At Microelec~ronics Center Of North Carolinamentioning
confidence: 99%
“…An alternative mechanism of vacancy generation is the growth of interstitial defects. These may be small interstitial dislocation loops as found earlier in transmission electron microscopy (1,2). Also a climbing dislocation is a source of vacancies by the growth of the extra half-plane.…”
Section: Discussionmentioning
confidence: 93%
“…In Eq. [2] Ae is the emitter area, nio is the intrinsic carrier concentration for low impurity concentrations, Veb is the applied emitterbase voltage, and GD is the Gummel number of the base. This is given by N~ nio ~2 Gb= f--~-( n~, ~x [3] where Dn is the diffusion coefficient for electrons in the base, ni is the dope-dependent intrinsic carrier concentration, and the integration is carried out over the base (8).…”
Section: Electrical Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In each case, the energy to "peel off" an As atom is -1.5 eV, which is the same as the value of the reactivation activation energy Schwenker et a1. [6] extracted from their experimental data. Since EXAFS data established that in deactivated samples virtually all As atoms are second neighbors to each other, [7] we conclude that the dominant complexes in deactivated samples are As2V and As3V.…”
Section: Comples Diffusive Phenomena In Heavily Arsenic Doped Siliconmentioning
confidence: 99%